2021
DOI: 10.3390/ijms22031096
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Invariant Natural Killer T Cells Modified with CD38 or BCMA Chimeric Antigen Receptors for Multiple Myeloma

Abstract: Due to the CD1d restricted recognition of altered glycolipids, Vα24-invariant natural killer T (iNKT) cells are excellent tools for cancer immunotherapy with a significantly reduced risk for graft-versus-host disease when applied as off-the shelf-therapeutics across Human Leukocyte Antigen (HLA) barriers. To maximally harness their therapeutic potential for multiple myeloma (MM) treatment, we here armed iNKT cells with chimeric antigen receptors (CAR) directed against the MM-associated antigen CD38 and the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…A limitation of belantamab mafodotin is the frequent development of keratopathy, which may substantially impair quality of life (146). Other cell types, with different killing mechanisms, such as NK cells, invariant NKT cells, γδ T cells, or myeloid cells, can also be engineered to express a CAR (149,150). However, at this moment, in the absence of clinical data, it is unknown whether adoptive therapy with alternative cell types will be able to overcome resistance conferred by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of belantamab mafodotin is the frequent development of keratopathy, which may substantially impair quality of life (146). Other cell types, with different killing mechanisms, such as NK cells, invariant NKT cells, γδ T cells, or myeloid cells, can also be engineered to express a CAR (149,150). However, at this moment, in the absence of clinical data, it is unknown whether adoptive therapy with alternative cell types will be able to overcome resistance conferred by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“… NKT cell source Activation Expansion Target CS Generation Cancer Phase Ref. or No.NCT Healthy donors Auto feeder cells pulsed with α-Galcer IL-2 GD2 CD28/4–1BB/CD28+4–1BB Second/third Neuroblastoma Preclinical [69] Healthy donors Irradiated auto NKT-negative cells pulsed with α-Galcer IL-2 CD19 4–1BB Second B cell lymphoma Preclinical [94] Healthy donors Anti-CD3 antibody IL-2 CSPG4 CD28 Second melanoma Preclinical [72] Healthy donors Irradiated auto NKT-negative cells pulsed with α-Galcer IL-2, IL-7 and/or IL-21 CD19 4–1BB Second B cell lymphoma Preclinical [96] Healthy donors Irradiated auto PBMC pulsed with CD3/28 at 1:1 beads-to-cell IL-2 and/or IL-15 CD19 CD28/CD28+OX40 Second/third B cell lymphoma Preclinical [74] Healthy donors Irradiated auto NKT-negative cells pulsed with α-Galcer IL-2, IL-7 and/or IL-21 GD2 CD28/4–1BB/CD28/4–1BB Second/fourth Neuroblastoma Preclinical [71] Healthy donors Irradiated auto NKT-negative cells pulsed with α-Galcer IL-2, IL-7 and IL-15 CD38/BCMA CD28/4–1BB Second Multiple myeloma Preclinical [70] Autologous iNKT GD2 CD28 …”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…It is worth noting that CAR-iNKT cells containing 4–1BB costimulatory domain did not increase the production of IL-6, which is one of the important cytokines associated with cytokine release syndrome. 4–1BB may provide an effective co-stimulation for optimal expansion and function of iNKT cells [70] . At the same time, experiments have proved that 4–1BB costimulation leads to activation induced cell death (AICD) of CAR-iNKT cells, and found that the activity of death receptor dependent caspase-8 is higher than that containing CD28.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26] The immune regulatory potential and the rapid cytokine production of iNKT cells suggest that these cells may be harnessed for redirection with CAR. To this end, Poels et al 27 expressed CD38 or B cell maturation antigen-directed CARs in Va24-iNKT cells and demonstrated effective elimination of multiple myeloma (MM) cells. Additionally, Xu et al 28 demonstrated potent anti-tumor activity by GD2-directed CAR NKT cells against neuroblastoma cells.…”
Section: Natural Killer T Cellsmentioning
confidence: 99%